Effects of a death education based on narrative pedagogy in a palliative care course among Chinese nursing students - Zhu, Yuanyuan; Bai, Yamei; Wang, Aihong; Liu, Yuexian; Gao, Qinyi; Zeng, Zhi (Frontiers in Public Health, 2023)
Background: Death education has been confirmed to be an effective method to enhance nursing students' attitudes and coping abilities towards death. However, integrated Narrative Pedagogy into the death education to explore educational effectiveness is still limited. The study aimed to evaluate the effects of a death education based on Narrative Pedagogy in a palliative care course on the death attitude attitude towards death, coping with death, and attitude towards caring for the dying among undergraduate nursing students in China.The study was designed as a pre-post intervention study with a quasi-experimental design. All the participants received 6 class hours of death education which was designed in a palliative care course. The death education includes preparation, presentation, discussion, reflection, and practice of the narrative materials. Death Attitude Profile-Revised (DAP-R), Coping with Death Scale (CDS), and Frommelt Attitude Toward Care of the Dying-Form B (FATCOD-Form B) were used to measure outcomes. Results: Sixty undergraduate nursing students who consented. There were statistically significant increases in the mean score of neutral acceptance and approach acceptance in the DAP-R, CDS, and FATCOD-Form B before and after the intervention. Conclusions: This death education integrated Narrative Pedagogy which indicated to improve death attitudeattitude towards death, competence to cope with death, and attitude toward the care of dying patients. The findings assist teachers in understanding the importance and urgency of death education, as well as providing a favorable approach to death education. However, the long-term effectiveness still needs to study in further.